THE INFLUENCE OF CUSTOMER EXPERIENCE AND PERCEIVED PRICE ON CUSTOMER SATISFACTION OF RIAU UNIVERSITY STUDENTS GoRide’s USER IN PEKANBARU - Chairani Asyuni; Lie Othman (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Investigating how perceived price and customer experience affect customer satisfaction among Riau University students using GoRide in Pekanbaru is the aim of this study. This study employs a quantitative methodology, collecting data through surveys and doing multiple linear regression analysis using IBM SPSS 25 software. Purposive sampling was used for the sampling procedure, and 384 respondents in all participated. The results of the study show that perceived price and customer experience have a big impact on customer satisfaction, at least in part. Additionally, customer satisfaction is impacted by both perceived price and customer experience at the same time. The results suggest that GoRide should maintain and improve services, especially in aspects such as sensory and physical experiences, while ensuring competitive prices to increase overall customer satisfaction. Keywords: Customer Experience; Perceived Price; Customer Satisfaction